Investigating collaborative learning in architectural design studios from the instructors' perspective - Karimi, Hirou; Farivarsadri, Guita (Emerald Group Publishing Ltd, 2025)
PurposeThis paper aims to examine the barriers to adopting collaboration in architectural design studios from the instructors' perspectives and explore strategies to overcome barriers.Design/methodology/approachSemi-structured interviews were conducted with 14 coordinators in architecture and interior architecture design studios to gather insights into their experiences and perspectives on collaboration. Thematic analysis was employed to identify key themes and patterns in the data.FindingsThe study reveals that collaboration is highly valued by instructors for its potential to enhance creativity, problem-solving abilities, and preparation skills among students. However, the study identified several barriers, such as student conflicts, coordination challenges, cultural differences, and technological constraints.Practical implicationsThe instructors recommended specific strategies to promote collaboration in architectural design studios. These strategies include involving students in collaborative projects, providing training in collaboration skills, striking a balance between online and in-person activities, and developing supportive policies and skills. Implementing these strategies can help design programmemes that prepare students for professional success and future careers.Originality/valueThis study sheds light on the importance of integrating collaboration skills in architectural education. By exploring barriers and suggesting strategies, it provides valuable insights for educators and encourages further research into the implementation of these strategies. Design programmes can benefit from adopting a multifaceted approach to foster collaboration among students, thereby enhancing their learning experience and future prospects.
Keywords: Collaboration; Architectural education; Design studios; Collaboration skills; Teamwork in education